Glomus Tumor of the Lower Extremity Previously Misdiagnosed as Complex Regional Pain Syndrome in Close Proximity to a Myxofibrosarcoma: A Case Report. (6th July 2022) - Nazemi, Alireza K.; Grossi, John; Tavernier, Felix B.; Boyce, Brendan F.; Komatsu, David E.; Khan, Fazel A.
Abstract : Complex regional pain syndrome (CRPS) is a potentially devastating condition that can result in severe psychological and social morbidity. It is a diagnosis of exclusion, and other pathologic entities must be ruled out first. Glomus tumors are exquisitely painful benign vascular tumors that are most common in the hand and are rarely found in the lower extremity. Here, we present a case of a patient who developed a focus of severe anterior knee pain and tenderness a few months after a car accident that had been misdiagnosed as CRPS for 15 years. She coincidentally developed a sarcoma of her ipsilateral leg distal to this site. Magnetic resonance imaging of the sarcoma included the area of knee pain where, interestingly, it identified a separate small soft-tissue mass. A glomus tumor was diagnosed histologically in a needle biopsy specimen from this mass, which was resected along with the sarcoma. For the first time in 15 years, despite the additional sarcoma surgery, she reported relief of her pain and complete resolution of her "CRPS."